Cyclic behavior of UHPFRC flexural members reinforced with high-strength steel rebar. (1st September 2016) - Hung, Chung-Chan; Chueh, Chen-Yu
Highlights: Cyclic behavior of innovative UHPFRC beams was experimentally investigated. UHPFRC beams were flexurally reinforced with high-strength steel rebar. The composite UHPC–UHPFRC beam was efficient and economical. The length of fibers had a significant effect on the structural performance. The flexural ductility increased along with the ratio of high-strength rebar. Abstract: Ultra-high performance fiber reinforced concrete (UHPFRC) is a unique class of fiber reinforced concrete. It features an ultra-high compressive strength and a ductile, tensile strain hardening behavior accompanied by multiple narrow cracking. The cyclic flexural performance of UHPFRC structural beams reinforced with high-strength steel with a specified yielding strength of 680 MPa is experimentally investigated in this study. Six cantilever beams are prepared and tested under displacement reversals. The experimental variables include the reinforcement ratio of the high-strength longitudinal rebar and the amount, location, and length of steel fibers in the beams. The intermediate and ultimate behaviors of these cantilever members are discussed using multiple performance parameters, including strength capacity, flexural ductility, failure pattern, hysteretic response, energy dissipation capacity, and stiffness retention. The results show that UHPFRC beams reinforced with high-strength steel are able to show satisfactory cyclic flexural performance prior to failure. The addition of steel fibers substantially enhances the damage tolerance ability of the high-strength beams, even when the fibers are selectively used only in the top and bottom beam sections. The proposed composite of UHPFRC and high-strength steel rebar not only takes advantage of the ultra-high mechanical properties of both materials, but also resolves the issue of potential premature failure patterns associated with high-strength concrete and high-strength steel rebar.